Risk Factors for Occupational Fatigue in Construction Workers: A Systematic Review - Ghaisani, Dinda Adharia; Susilowati, Indri Hapsari (Jurnal Indonesia Sosial Sains, 2025)
Occupational fatigue is a common issue in various industries, particularly in the construction sector, which is characterized by high occupational risks. This study aims to identify the risk factors contributing to occupational fatigue among construction workers and propose strategies to mitigate these risks. The research employs a systematic literature review method following PRISMA guidelines. The literature search was conducted using Google Scholar, PubMed, and ScienceDirect with keywords such as “Occupational Fatigue,” “Work Fatigue,” “Construction Worker,” “Risk Factor,” and “Construction,” covering publications from 2014 to 2024. Articles were selected based on inclusion and exclusion criteria to ensure relevance. The review of 12 selected articles identified several key risk factors associated with occupational fatigue, including job complexity, work stress, psychological health conditions, age, tenure, work climate, workload, and unsafe working conditions. Additionally, a negative work climate, excessive workload, and hazardous work environments were found to be major contributors to workplace fatigue. The findings indicate that addressing these risk factors is essential for improving worker safety and well-being. Implementing targeted interventions, such as workload management, stress reduction programs, and improvements in occupational health and safety standards, can significantly reduce fatigue levels among construction workers. These measures can also enhance productivity and overall job satisfaction in the construction industry.